Benefit Sharing in Practice : Insights for REDD+ Initiatives - Chandrasekharan Behr, Diji; Mairena Cunningham, Eileen; Kajembe, George; Mbeyale, Gimbage; Nsita, Steve; Rosenbaum, Kenneth L. (Program on Forests (PROFOR), Washington, DC, 2013)
Reducing emissions from deforestation and forest degradation and enhancing carbon stocks (REDD+) has raised the profile of benefit sharing in the forest sector. Sharing benefits, however, is not a new concept. Previous work on benefit sharing (associated with intellectual property, forest and agriculture concessions, mining, and so forth) has focused on clarifying the concept and examining how benefit sharing could feed into broader development outcomes. Getting benefit sharing right in the context of REDD+ has a similar objective. The objective of this study is twofold. The first is to examine existing arrangements for sharing benefits and extract insights from existing community-based natural resource management (CBNRM) arrangements that involve sharing benefits, specifically insights regarding how benefits are determined, how beneficiaries are identified, and how the set-up is influencing the effectiveness of the arrangements. The second objective is to provide community perspective on benefit sharing and partnerships in the forest sector. This study examines nine partnership arrangements in three countries Nicaragua, Tanzania, and Uganda. The partnerships include five performance-based PES arrangements (of which two are focused on carbon). The remaining four partnerships involve sustainable management of forests for specific objectives (timber, ecotourism, wildlife conservation, and so forth). All the partnerships took several years to set up, and some have been under implementation for several years. For purposes of this study, benefit sharing or sharing of benefits refers to an intentional transfer of financial payments and payments in the form of goods and services to intended beneficiaries.